2014
DOI: 10.1016/j.ecoenv.2014.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum concentrations of perfluoroalkyl acids and serum lipid levels in a Chinese population

Abstract: a b s t r a c tPerfluoroalkyl acids (PFAAs) have been used in a variety of products for many years and have been detected worldwide in human serum. Previous studies have suggested the potential effects of PFAAs on serum lipids. To investigate the associations between serum concentrations of PFAAs and serum lipid levels, 133 participants were randomly selected from the people coming for health check-up in Yuanyang Red Cross Hospital of Henan, China. Linear regression analysis revealed that perfluoro-octanoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 53 publications
(70 reference statements)
4
53
3
Order By: Relevance
“…To summarize, we have shown that C57BL/6 and male BALB/c mice exposed to PFOA have significantly increased plasma cholesterol levels when fed Westernized diets, consistent with human observational findings at the national [39] , [14] and community levels [16] , [19] , [60] and in adolescent [18] , [20] and occupational [44] , [56] , [57] , [9] cohorts. As the majority of these human studies are cross-sectional and unable to assess causality, it has been difficult to study causality because of the directionality difference between epidemiologic human and experimental rodent studies [46] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To summarize, we have shown that C57BL/6 and male BALB/c mice exposed to PFOA have significantly increased plasma cholesterol levels when fed Westernized diets, consistent with human observational findings at the national [39] , [14] and community levels [16] , [19] , [60] and in adolescent [18] , [20] and occupational [44] , [56] , [57] , [9] cohorts. As the majority of these human studies are cross-sectional and unable to assess causality, it has been difficult to study causality because of the directionality difference between epidemiologic human and experimental rodent studies [46] .…”
Section: Discussionsupporting
confidence: 83%
“…In our mice, the increase in plasma cholesterol occurred in the HDL fraction. In humans, significant increases in LDL with increasing PFOA have been seen in national adolescent studies [20] , [75] , exposed communities [60] , [16] , [18] , [19] and occupational cohorts [56] . Human HDL cholesterol and PFOA studies are less consistent, though all show a decrease in HDL as PFOA increases [20] , [21] , [47] , [66] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, CYP7A1 deficiency promotes hypercholesterolemia (Beigneux et al, 2002, Pullinger et al, 2002). Epidemiological evidence of individuals exposed to PFOA or PFOS suggest a positive correlation between exposure and increased serum cholesterol (Fu et al, 2014, Geiger et al, 2014, Kerger et al, 2011). Thus, the observed increase in cholesterol in humans exposed to PFOA or PFOS potentially results from a loss of HNF4α function and decreased CYP7A1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al. () performed a small (N = 133) cross‐sectional study of the association between PFOS and PFOA and blood lipids in a Chinese sample aged 0–80 (mean 30) years, coming for a health check‐up. Analyses were adjusted for age, gender and BMI, but there was no information on use of lipid‐lowering medications.…”
Section: Assessmentmentioning
confidence: 99%